The effect of incubation time and temperature on sperm motility, human sperm DNA and assisted reproductive technologies (ART) outcome - Van Zyl, Estee Alwelien (Stellenbosch : Stellenbosch University, 2015)
Thesis (MMed)--Stellenbosch University, 2015.